Implementasi Sistem Retensi File Rekam Medis di Rumah Sakit - Fitria Aryani Susanti; Malihah Ramadhani Rum (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2024)
The large number of medical record archives produced must be balanced with the retention process so that the ever-increasing medical record archives do not result in accumulation in the processing unit and do not disrupt the smooth working process. The aim of this research is to look at the implementation of the medical record document retention system at Prikasih Hospital so that problems can be identified and a follow-up plan prepared so that the medical record document retention system can be implemented well. The type of research used is descriptive research using qualitative methods with the aim of obtaining information regarding the description of the retention system process. For human resources, it was found that the level of education did not comply with the qualification standards set by Minister of Health Regulation No. 55 of 2013, Prikasih Hospital Jakarta already has standard operational procedures but does not yet have a Records Retention Schedule (JRA). The infrastructure is inadequate because Prikasih Hospital Jakarta does not yet have a special room for storing inactive medical records.